Cultural Diversity as a Part of Sustainable Development and Culturally Responsive Teaching - Dejan M. Đorđić (University of Belgrade, Teacher Education Faculty, 2019)
As cultural diversity is a given of the society that we live in, and it is necessary that the society, and education as its integral part, defines its attitude towards cultural diversity in the age of globalization. In its publications, UNESCO defined the preservation of cultural diversity as an integral and indispensable part of sustainable development, and this is particularly emphasized in the 2001 Universal Declaration on Cultural Diversity and the 2005 Convention on the Protection and Promotion of the Diversity of Cultural Expression. Education is viewed as a key process in which different cultural values, both national and universal, can be conveyed. The concept of culturally responsive pedagogy is emerging with a growing awareness of cultural differences and the need to nurture them. The need for the preservation of cultural heritage and tradition along with a top academic achievement is the starting point of the culturally responsive pedagogy. It focuses not only on the teaching process, but also on broader social elements that lead to the liberalization of teaching culturally diverse students. The aim of the paper is to look at the importance of cultural diversity through key documents and to consider the assumptions of the culturally responsive pedagogy as a response to cultural diversity, given that sustaining cultural diversity is a part of sustainable development.